Penerapan Aplikasi Pegadaian Digital Service Dalam Transaksi Gadai Pada PT. Pegadaian ( Persero ) UPC Katamso Medan - Syahfrilla Al Risa Nurul Azmi; Budi Dharma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
PT. Pegadaian (Persero) is a non-bank financial institution which is legally permitted to carry out credit financing on the basis of pawn law. PT. Pegadaian is currently carrying out transformation in the digital world by creating a web-based application called